Treatment in disproportionately minority hospitals is associated with increased risk of mortality in sepsis: a national analysis - Rush, Barret (Crit Care Med, 2020)
OBJECTIVE: Treatment in a disproportionately minority serving hospital has been associated with worse outcomes in a variety of illnesses. We examined the association of treatment in disproportionately minority hospitals on outcomes in patients with sepsis across the United States. DESIGN: Retrospective Cohort Analysis SETTING: The National Inpatient Sample from 2008–2014 METHODS: Disproportionately minority hospitals were defined as hospitals having twice the relative minority patient population than the surrounding geographical mean. Minority hospitals for Black and Hispanic patient populations were identified based on US Census demographic information. A multivariate model employing a validated algorithm for mortality in sepsis using administrative data was utilized. INTERVENTIONS: None MEASUREMENTS AND MAIN RESULTS: A total of 4,221,221 patients with sepsis were identified. Of these, 612,217 (14.5%) patients were treated at hospitals disproportionately serving the black community (Black hospitals) while 181,141 (4.3%) were treated at hospitals disproportionately serving the Hispanic community (Hispanic hospitals). After multivariate analysis, treatment in a Black hospital was associated with a 4% higher risk of mortality compared to treatment in a non-minority hospital (OR 1.04, 95% CI 1.03–1.05, p<0.01). Treatment in a Hispanic hospital was associated with a 9% higher risk of mortality (OR 1.09, 95% CI 1.07–1.11, p<0.01). Median hospital length of stay was almost 1 day longer at each of the disproportionately minority hospitals (5.9 days IQR 3.1–11.0 Non-Minority Hospitals vs 6.9 days IQR 3.6–12.9 Hispanic and 6.7 days IQR 3.4–13.2 Black, both p<0.01). CONCLUSION: Patients with sepsis regardless of race who were treated in disproportionately high minority hospitals suffered significantly higher rates of in-hospital mortality.